Partisipasi Masyarakat Dalam Pengembangan Mts Misbahul Fatah Klenang Kidul Banyuanyar Probolinggo - Junaedi, Achmad; Zaini, Muhammad (LP3M UNZAH GENGGONG, 2020)
ABSTRACT Madrasah as formal educational institutions that have differences in education management are increasingly needed. Therefore, collaboration between the community and institutions must be developed synergistically, bearing in mind the same interests and ideals, namely saving and enlightening the future of the nation's generation. This study aims to describe and analyze community participation in the development of human resources (HR) and the development of facilities and infrastructure for Madrasah Tsanawiyah Misbahul Fata Klenang Kidul Banyuanyar Probolinggo. This research is a qualitative descriptive study, taking the research location at Madrasah Tsanawiyah Misbahul Fata Klenang Kidul Banyuanyar Probolinggo. Data collection techniques using observation, interviews, and documentation. Data analysis in this study used single site data analysis and cross site analysis. Checking the validity of the data used data triangulation techniques. The results showed that: First, community participation in the development of human resources in Madrasah Tsanawiyah by fostering conditions of openness and mutual trust, and establishing good communication with the community. Community participation is carried out in the form of decision making, program implementation, program utilization and evaluation of madrasah programs facilitated and bridged by madrasah which function to accommodate the aspirations and needs of the community as well as mobilize and channel community participation in the education sector. Second, community participation in the development of facilities and infrastructure for Madrasah Tsanawiyah can be seen from the participation of the community in contributing to their ideas by planning the procurement of infrastructure needed by madrasah, and proposing for consideration of the management of the madrasah budget plan (RABM). Community participation is realized by providing educational support facilities in the form of mosques, football fields and residents' houses. Keywords: Community Participation, Human Resources, Infrastructure